2001
DOI: 10.1074/jbc.m004942200
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Thrombomodulin Gene Transcription by Retinoic Acid

Abstract: The interactions between retinoic acid-(RA)-dependent transcriptional regulatory sequences of the 5-untranslated region of the thrombomodulin gene and nuclear RA-responsive proteins were studied using human pancreas BxPC-3 cells. Deletion mutants of pTM-CAT plasmid revealed the presence of distal and proximal RA-responsive regions containing direct repeat with 4 spaces (DR4) and three of four Sp1 sites, respectively. Cotransfection of a pTM-CAT plasmid with expression plasmids of RA receptors (RAR␣, RAR␤, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 71 publications
(28 reference statements)
1
14
0
Order By: Relevance
“…This could be due to a RA-induced change in the phosphorylation state of Sp1. 37,38 Similar results have been reported with GC-box motifs derived from promoters of other genes expressed in the endothelium. 37,39,40 We also identified RAR␤ and RAR␥ as DR5 binding proteins.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This could be due to a RA-induced change in the phosphorylation state of Sp1. 37,38 Similar results have been reported with GC-box motifs derived from promoters of other genes expressed in the endothelium. 37,39,40 We also identified RAR␤ and RAR␥ as DR5 binding proteins.…”
Section: Discussionsupporting
confidence: 77%
“…Despite this, several attempts to detect a DNA-protein complex containing both RAR/RXR and Sp1 have failed. [38][39][40] However, Husmann et al, 44 who studied a GC-box in the interleukin 1B promoter, detected a RAR-Sp1-GCbox complex by EMSA when using RAR fusion protein and recombinant Sp1. On the basis of the results of our study, we speculate that the polymorphic GC-box and the DR5 site may be a functionally coupled transcriptional unit that is quantitatively influenced by the SNP at position Ϫ7351.…”
Section: Discussionmentioning
confidence: 99%
“…An Sp1 binding motif within the GT box-containing element was predicted by sequence analysis using the Transfac database. Sp1 was found to interact with the heterodimer RAR-RXR in the regulation of thrombomodulin gene transcription by retinoid acid (28). This motivated a test of whether an Sp1 consensus sequence oligonucleotide would compete with the GT box-containing element.…”
Section: Activation Of Rar␣ and Rxr␣ Expressed In Hl-60 Cells Inducesmentioning
confidence: 99%
“…It has been reported that tandem GC box sequences exist in several gene promoters, such as prostacyclin synthase (35), thromboxane receptor (36), hemopoietic cell kinase (37), Nmethyl-D-aspartate receptor 1 (38), and thrombomodulin (39,40). These tandem GC boxes represent binding sites for members of the Sp1 transcription factor family (41) that play an important role in the control of transcription of the aforementioned genes.…”
Section: Fig 4 Effects Of Gc Box Mutations On the Mouse Mpges Promomentioning
confidence: 99%